Preface - Almeida, João P. (2023)
The XXI Congress of APDIO, the Portuguese Operational Research Society, took place on 7 and 8 November 2021, with more than 120 registered participants and around 80 papers submitted. This congress took place at a very particular historical moment. After the first waves of the COVID-19 pandemic, which had immobilized humanity, cancelling all gatherings, society was equipped with the first effective weapons against the pandemic, in particular vaccines, and the world was beginning to reopen. Science, in all its facets, had been massively called upon for this on a scale that humanity had never before experienced. It was in this context of hope that the APDIO congress took place, also celebrating the significant contribution of this discipline in fighting the pandemic. Thus, “Analytics for a BetterWorld” was chosen as the congress theme.